Competition, strategic delegation and delay in technology adoption. Issue 2 (17th February 2016) - Mahathi, A.; Pal, Rupayan; Ramani, Vinay
Abstract : This paper examines how strategic managerial delegation affects firms' timing of adoption of a new technology under different modes of product market competition. It demonstrates that strategic delegation has differential impacts on adoption dates under Cournot and Bertrand competitions. Strategic delegation with 'own-performance'-based incentive schemes always leads to early adoption in markets with Bertrand competition compared to that under no-delegation, but not necessarily so in markets with Cournot competition. It also shows that under strategic delegation with 'own-performance'-based incentive schemes, adoption occurs earlier (later) in markets with Cournot competition than in markets with Bertrand competition, if the degree of product differentiation is high (low). In contrast, under strategic delegation with 'relative-performance'-based incentive schemes, adoption dates do not differ across markets with different modes of competition. It also analyses implications of firms' choice over types of managerial incentive schemes on the speed of diffusion of new technology.